The Influence of Inflation, Exchange Rates, and Profit Sharing Amounts on Muharabah Deposits in Sharia Banks (Study of Aceh Sharia banks for the 2018-2022 period) - Muhammad Hafizh; Cut Putri Ajmadayana (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
This study aims to look at the effect of inflation, exchange rates, and profit sharing on muharabah deposits at Islamic banks (Aceh Syariah bank study for the 2018-2022 period. The data used in this research is secondary data for the 2018-2022 period. The method used to analyze the relationship between variables namely multiple regression.The results showed that partially inflation had no effect on mudharabah deposits at Bank Aceh Syariah, the exchange rate had a positive and significant effect on mudharabah deposits at Bank Aceh Syariah.Profit sharing had a positive and significant effect on mudharabah deposits at Bank Aceh Sharia This shows that the higher the profit sharing, the mudharabah deposits will increase Simultaneously inflation, exchange rates and profit sharing have a positive and significant effect on mudharabah deposits at Bank Aceh Syariah.